Pengaruh Likuiditas, Profitabilitas, dan Leverage Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderating Pada Perusahaan SubSektor Kontruksi dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Kusumawati, Qomaria Ayu; Pranjoto, R Gatot Heru (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The purpose of this study was to determine the effect of Liquidity, Profitability, and Leverage on Profit Growth with Company Size as a Moderatating variable. The type of research used is a type of quantitative research using secondary data with data sources derived from financial reports. The sample in this study was obtained by purposive sampling method with a total sample of 14 companies from 18 companies. The data analysis technique used is the classical assumption test, moderating regression analysis and hypothesis testing using SPSS Version 26. Based on the results of this study indicate that (1) Current Ratio has a negative and in significant effect on Profit Growth. (2) Net Profit Margin has a negative and insignificant effect on Profit Growth. (3) Debt to Equity Ratio has a positive and insignificant effect on Profit Growth. (4) Company Size cannot moderate the Current Ratio, Net Profit Margin, and Debt to Equity Ratio